Reimagining community engagement in TB elimination: a perspective from the field - A. Ashesh; C. Mehra; V. Madan; J. Furin (IJTLD Open)
The role of community engagement (CE) in TB policy, care provision and research has been recognized as important, but most models of CE put communities at the periphery of these activities. In this Editorial, written by TB-impacted community members and care providers, we explore the meaning of CE and current barriers to its implementation. We present a model of CE that places community members at the center of TB policy, care provision and research. The article concludes with advocacy points, including the need for sufficient funding for CE and genuine power-sharing between TB-affected communities and the people and programs aiming to serve them.